Identification of 5-Methoxy-2-(Diformylmethylidene)-3,3-Dimethylindole as an Anti-Influenza A Virus Agent - Tan, M.C.; Wong, W.Y.; Ng, W.L.; Yeo, K.S.; Mohidin, T.B.M.; Lim, Y.Y.; Lafta, F.; Mohd Ali, H.; Ea, C.K. (Public Library of Science, 2017)
Influenza virus is estimated to cause 3-5 million severe complications and about 250-500 thousand deaths per year. Different kinds of anti-influenza virus drugs have been developed. However, the emergence of drug resistant strains has presented a big challenge for efficient antiviral therapy. Indole derivatives have been shown to exhibit both antiviral and anti-inflammatory activities. In this study, we adopted a cell-based system to screen for potential anti-IAV agents. Four indole derivatives (named 525A, 526A, 527A and 528A) were subjected to the antiviral screening, of which 526A was selected for further investigation. We reported that pre-treating cells with 526A protects cells from IAV infection. Furthermore, 526A inhibits IAV replication by inhibiting the expression of IAV genes. Interestingly, 526A suppresses the activation of IRF3 and STAT1 in host cells and thus represses the production of type I interferon response and cytokines in IAV-infected cells. Importantly, 526A also partially blocks the activation of RIG-I pathway. Taken together, these results suggest that 526A may be a potential anti-influenza A virus agent.